Tourism based on nature : The Kota Kinabalu experience / Juinen Jullan... [et al.] - Jullan, Juinen; Justina, David; Toidis, Nicholas; Kiop, Lauvon (Perpustakaan Tun Abdul Razak UiTM Caw Sabah, 2004)
Tourism as an industry often becomes more complex than it already is when it involves a combination of such diverse elements as the natural environment, cultural heritage and modern comforts. In Sabah, the emphasis of overseas promotion by both the government and the private sector has been on nature and all that it entails, such as adventure sports and physical recreation. The good news is that Sabah is fortunate to still have a relatively unpolluted or uncorrupted natural environment that is obviously necessary to support nature-based tourism. The bad news is the flipside - the paradox that "tourism kill’s tourism", a self-destruct phenomenon that can result from indiscriminate or excessive tapping of tourism resources. In an era when global sensitivity to any real or perceived threat to the natural environment is at all-time highs, countries with nature as the anchor of their tourism products are in the limelight, and not always in a positive way. Phrases like "eco-friendly", "sustained development" and "carrying capacity" are thrown about like fashion statements, and quickly accepted by the mass media. Never mind whether or not those who utter these words believe in them strongly enough to practice what they preach or at least lend support to those who do. What truly matters first and foremost is general awareness. A deeper understanding can come later and as history suggests, it most likely will, ~ though not necessarily in the same generation. JV There have also been numerous efforts to instill conservation awareness among the young, from the small-scale district-level cleanliness campaigns to national and global campaigns such as recycling. The Sabah State government also hopes for greater awareness among rural communities judging from the undertones of public events. Various forms of "pesta" or festivals are organized as annual events in various districts, usually themed after local produce such as coconut, rumbia (a member of the palm family with edible trunk) and bamboo. In each case, the local community is told that their participation can determine the success of the pesta and help improve their economic status. Although not exclusively for tourism purposes, these festivals are promoted as tourist attractions. The support of the local community has been acknowledged as a prerequisite to the success of tourism as an important industry and therefore, a major contributor to the economy of the state. This, of course, is not a new discovery but a lesson learnt from the experiences of other more established tourist destinations.